Carbon foorprint for hostel construction using industrialised building system in Pauh Putra, Perlis / Norashikin binti Razali - Norashikin Razali (School of Environmental Engineering, Universiti Malaysia Perlis, 2018)
This study uses LCA analysis frameworks to measure the total amount of carbon footprint consumption in the manufacturing factory and construction site activity. The objectives of this study are ; to identify IBS Content Scoring System (IBS Score) for five-storey hostel construction building ; to measure the total amount of indirectcarbon footprint in prefabricated sandwich panel (PSP) manufacturing factory in regards to machinery usage ; to measure the total amount of direct carbon footprint for materials and machinery during PSP installation in construction site.